A description of the system of registration and transfer of land titles and securities in the Canton Vaud - O'Brien, Murrough (Statistical and Social Inquiry Society of Ireland, 1890)
The introduction of a Land Transfer Bill for England, and of a Bill to establish Local Registries of Title in Ireland, mark a distinct advance in public opinion on this important question, which, though often the subject of papers here, may be usefully re-discussed by our Society when a radical change in the law is imminent.
Read Tuesday, 28th January, 1890
Keywords: Land transfer record; Canton Vaud; 314.15